A study on the structural transition in the plastic layer during coking of Australian coking coals using Synchrotron micro-CT and ATR-FTIR. (1st December 2018) - Lee, Soonho; Yu, Jianglong; Mahoney, Merrick; Tremain, Priscilla; Moghtaderi, Behdad; Tahmasebi, Arash
Highlights: The structural transition inside the plastic layer is studied. Drastic structural changes inside the plastic layer took place during coking process. Synchrotron micro-CT results showed physical structure transition in plastic layer. The vitrinite content and coal rank strongly affected the structure of plastic layer. Abstract: The chemistry of the plastic layer in a coke oven plays a critical role in coke-making and has a great impact on coke quality. In this study, progressive changes of the plastic layer were investigated using a combination of analytical methods. Three Australian coking coals with different vitrinite contents were used to produce plastic layer samples using a 4 kg lab-scale coke oven. The plastic layer samples were analysed by means of Synchrotron micro-CT scanning and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) analysis to delineate the characteristic regions of each layer. The peak separation and quantitative calculation of FTIR spectra allowed the analysis of changes in structural parameters and functional groups of each plastic layer. The results showed drastic changes in physical and chemical structures of the plastic layer samples for all coals tested and were also strongly influenced by coal type. For the high-vitrinite coals, it seems that relatively larger amounts of the plastic mass were developed due to the timely rupture of large number of the bridge bonds in the intermediate plastic regions and efficient hydrogen transfer to stabilize the radicals generated. This led to a more drastic growth of pores and larger maximized porosities in the intermediate plastic regions. Conversely, the low-vitrinite coal was assumed to form lower amount of the plastic mass in the intermediate plastic region due to less rupture of aliphatic bridge bonds and inefficient hydrogen transfer. This was attributed to a lower degree of the pore development and the lower porosity observed in the region.